2012
DOI: 10.1007/s00531-012-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of Pleistocene Rhine River Middle Terrace sands between the Swiss–German border and Cologne based on U–Pb detrital zircon ages

Abstract: Detrital zircon U-Pb age distributions derived from samples representing ancient or relatively young large

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 90 publications
(128 reference statements)
3
28
0
Order By: Relevance
“…Similarly, Krippner & Bahlburg (2013) studied Pleistocene Rhine sand and demonstrated that a complete orogenic cycle (the Alps) can be overlooked with zircon age data.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Krippner & Bahlburg (2013) studied Pleistocene Rhine sand and demonstrated that a complete orogenic cycle (the Alps) can be overlooked with zircon age data.…”
Section: Discussionmentioning
confidence: 99%
“…; Andersson et al . ; Krippner & Bahlburg ; and references therein). Proterozoic to Archean rocks are, however, typical not only of Scandinavian and Baltic areas, but also of the Bohemian Massif and the Ukrainian Platform in Europe (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rivers of the CERS were responsible for the delivery of material sourced from Palaeozoic to Mesozoic metamorphic terrains in western and central Europe whose exhumation ages date to Mesozoic and Tertiary times (Spiegel et al . ; Krippner & Bahlburg ; Reiter et al . ; Glotzbach et al .…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…garnet, epidote, hornblende, tourmaline and zircon), their proportions and/or U-Pb age dating of zircons.The latter method is valuable for characterisering the provenance areas of sediments. It brought Krippner & Bahlburg (2013) to question the commonly made assumption of a direct delivery of detritus to the downstream Rhine river system from the Alps during at least some parts of the Pleistocene. This would also necessitate the re-evaluation of explanations on the provenance of Dutch sediments.…”
Section: Heavy Mineralsmentioning
confidence: 99%